Directional bilateral asymmetry in otolith morphology may affect fish stock discrimination based on otolith shape analysis. (15th November 2018) - Mahé, Kélig; Ider, Djamila; Massaro, Andrea; Hamed, Oussama; Jurado-Ruzafa, Alba; Gonçalves, Patrícia; Anastasopoulou, Aikaterini; Jadaud, Angelique; Mytilineou, Chryssi; Elleboode, Romain; Ramdane, Zohir; Bacha, Mahmoud; et al.
Abstract: Otolith shape analysis is an efficient fish stock identification tool. However, most applications used left and right otoliths or only one of them arbitrarily chosen without testing for biases resulting from potential directional bilateral asymmetry (DA) in otolith shape, i.e. a unimodal population-level deviation form bilateral symmetry between right and left otolith shapes. In this study, 560 bogues ( Boops boops ) were sampled from 11 geographical locations from the Canary Islands to the Aegean Sea and elliptical Fourier descriptors were used to describe their otoliths' shape. First, a significant otolith DA was observed at the global scale with an average amplitude of 2.77%. However, at the scale of sampling locations, DA was not always significant and varied in amplitude and direction. Second, population structure was investigated using the shape of either right otoliths or left otoliths or both together. Analyses based on right otoliths or both otoliths together, suggested three stock units: a North-Western Mediterranean Sea stock, an Eastern Mediterranean Sea stock, and a Central-Eastern Atlantic Ocean and South-Western Mediterranean Sea stock. In contrast, no coherent geographical pattern was found based on left otoliths. Our results highlight the importance of accounting for potential otolith DA in otolith shape-based stock identification.